PENGARUH KEPEMIMPINAN KEPALA MADRASAH TERHADAP MOTIVASI DAN DISIPLIN KERJA GURU NON SERTIFIKASI DI LOMBOK TIMUR - Rahmatullah, Muh Hilmi; Muhammad, Muhammad; Citriadin, Yudin; Fauziah, Nurul (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of madrasah principal leadership on the work motivation and work discipline of non-certified teachers at private Tsanawiyah madrasahs in Sakra Barat District. This study employs a quantitative approach, utilizing a survey research design. The population in this study consists of 193 non-certified teachers spread across 16 madrasahs. The sampling technique used is a census sample. Therefore, the sample in this study amounts to 193 teachers. The data processing in this study is carried out with the assistance of the Partial Least Square (PLS) application. The results of this study indicate that the leadership of the madrasah principal has a positive and significant influence on the work motivation of non-certified teachers. The leadership of the madrasah principal also has a positive and significant effect on the work discipline of non-certified teachers. Furthermore, work motivation has a positive and significant impact on the work discipline of non-certified teachers at Tsanawiyah madrasahs in Sakra Barat District. This study implies that madrasah principals must continuously improve the quality of their leadership by applying an effective leadership style, being exemplary figures, and acting as motivators for teachers.